THERMOCHEMISTRY OF AG2S-CU2S SULFIDE SOLUTIONS: CONSTRAINTS DERIVED FROM COEXISTING SB2S3- AND AS2S3-BEARING SULFOSALTS - Harlov D.E.; Sack R.O. (My University, 1995)
We report experimental brackets (150-350°C, evacuated silica tubes) on (1) Ag-Cu partitioning between hexagonally close packed (hcp)-, face centered cubic (fcc)-, and body centered cubic (bcc)-(Ag, Cu)2S sulfides and the sulfosalts polybasite-pearceite [(Ag1-xCux)16(Sb, As)2S11, 0.10 < x < 0.57] and high-skinnerite [(Cu1-x, Agx)3SbS3, x < 0.26] and (2)Ag ratios of (Ag, Cu)2S sulfides coexisting with polybasite and skinnerite, and polybasite and pyrargyrite [(Ag1-x, Cux)3SbS3,x < 0.21]. Based on these brackets on Ag-Cu partitioning and activity-composition models for polybasite-pearceite and high-skinnerite (Harlov and Sack, 1994, 1995) we infer that (1) both hcp- and bcc-(Ag, Cu)2S sulfides exhibit positive deviations from ideality sufficient to produce metastable unmixing at slightly less than 90°C and (2) fcc-(Ag, Cu)2S sulfides display more moderate positive deviations from ideal activity-composition relations, characterized by a regular-solution-type parameter, WfccAg-Cu = 5.4 +/- 0.2 kJ/mol, for an assumed site multiplicity of Ag-Cu mixing of 2. The inferred activity-composition relations for fcc- and bcc-(Ag, Cu)2S are consistent with brackets on the T - XCu systematics of the transition between these phases (Skinner, 1966) and the calorimetric data of Gronvold and Westrum (1986) for Ag2S provided that the effective site multiplicity of Ag-Cu mixing in bcc-(Ag, Cu)2S decreases linearly from about 3 in Cu-poor to about 2 in Cu-rich compositions (XCu # 0.315). Our constraints are also consistent with the calorimetric data for Cu2S (Gronvold and Westrum, 1987) and Skinner's (1966) brackets on the T - XCu systematics of the transition between fcc- and hcp-(Cu, Ag)2S provided that the effective site multiplicity of Ag-Cu mixing in hcp-(Ag, Cu)2S approximates 3. From our brackets on Ag ratios of (Ag, Cu)2S sulfides coexisting with polybasite and skinnerite, and polybasite and pyrargyrite and calibrations for the Ag-Cu exchange reactions we calculate average values of 5.30 +/- 1.14 and -31.1 +/- 0.7 kJ/mol for the Gibbs energies of formation of hypothetical Cu16Sb2S11 and Ag16Sb2S11 polybasite components from the simple sulfides over the temperature range 150-350°C.